The Role of Axon Transport in Neuroprotection and Regeneration - Shah, Sahil H. (Dev Neurobiol, 2018)
Retinal ganglion cells and other central nervous system neurons fail to regenerate after injury. Understanding the obstacles to survival and regeneration, and overcoming them, is key to preserving and restoring function. While comparisons in the cellular changes seen in these non-regenerative cells with those that do have intrinsic regenerative ability has yielded many candidate genes for regenerative therapies, complete visual recovery has not yet been achieved. Insights gained from neurodegenerative diseases, like glaucoma, underscore the importance of axonal transport of organelles, mRNA, and effector proteins in injury and disease. Targeting molecular motor networks, and their cargoes, may be necessary for realizing complete axonal regeneration and vision restoration.